Redesign of Centrifugal Pump with Capacity 286.8 M3/hrs and Head 32 Metre at Karawang International Industrial City - Susilo Handoko; Hanif Arif Wibowo; Kasturi Kasturi (Politeknik Energi dan Mineral Akamigas, 2021)
Mechanical equipment has an important role to support the needs of a process. There is mechanical equipment, namely a pump that functions to move liquid fluid from one place to another through the piping medium. Based on report from customer, Centrifugal pump ETA-N 150 x 125 - 315 which functions as supply distribution of clean water from Water Treatment Plant (WTP) to the Karawang area International Industrial City (KIIC) experienced a decrease in capacity and Head and happened unbalance on the pump drive motor rotor. After an investigation by the team engineering PT. TG Engineering, found problems such as heavy corrosion and corrosion erosion on surface impeller, spoons impeller and volute chamber, deep scratch and light corrosion on shaft / shaft, as well as malfunction bearing on bearing pump and bearing pump drive motor unbalance. Referring to the results of the investigation, the authors design and select centrifugal pump components based on the results of the investigation. So that after calculating the dimensions of impeller, shaft, key and component selection such as type bearing, lubrication bearing, as well as coupling.